Changing environments during the Middle-Upper Palaeolithic transition in the eastern Cantabrian Region (Spain): direct evidence from stable isotope studies on ungulate bones. Issue 1 (December 2018) - Jones, Jennifer; Richards, Michael; Straus, Lawrence; Reade, Hazel; Altuna, Jesús; Mariezkurrena, Koro; Marín-Arroyo, Ana
Abstract Environmental change has been proposed as a factor that contributed to the extinction of the Neanderthals in Europe during MIS3. Currently, the different local environmental conditions experienced at the time when Anatomically Modern Humans (AMH) met Neanderthals are not well known. In the Western Pyrenees, particularly, in the eastern end of the Cantabrian coast of the Iberian Peninsula, extensive evidence of Neanderthal and subsequent AMH activity exists, making it an ideal area in which to explore the palaeoenvironments experienced and resources exploited by both human species during the Middle to Upper Palaeolithic transition. Red deer and horse were analysed using bone collagen stable isotope analysis to reconstruct environmental conditions across the transition. A shift in the ecological niche of horses after the Mousterian demonstrates a change in environment, towards more open vegetation, linked to wider climatic change. In the Mousterian, Aurignacian and Gravettian, high inter-individual nitrogen ranges were observed in both herbivores. This could indicate that these individuals were procured from areas isotopically different in nitrogen. Differences in sulphur values between sites suggest some variability in the hunting locations exploited, reflecting the human use of different parts of the landscape. An alternative and complementary explanation proposed is that there were climatic fluctuations within the time of formation of these archaeological levels, as observed in pollen, marine and ice cores.